2001
DOI: 10.1111/j.0014-3820.2001.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Offspring Viability as a Manifestation of Aging in Drosophila Melanogaster

Abstract: Abstract. The evolutionary explanation of senescence proposes that selection against alleles with deleterious effects manifested only late in life is weak because most individuals die earlier for extrinsic reasons. This argument also applies to alleles whose deleterious effects are nongenetically transmitted from mother to progeny, that is, that affect the performance of progeny produced at late ages rather than of the aging individuals themselves. We studied the effect of maternal age on offspring viability (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
113
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 43 publications
10
113
1
Order By: Relevance
“…Generally measured as total adult offspring, fertility decreases with increasing maternal age ( 16,27,60,81 , although only 27 controls for male age). In the later study, young (3 d pe) females produced, on average, >250 offspring over 6 d while older females (28 d pe) produced >60% fewer offspring over the same duration.…”
Section: Fertilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Generally measured as total adult offspring, fertility decreases with increasing maternal age ( 16,27,60,81 , although only 27 controls for male age). In the later study, young (3 d pe) females produced, on average, >250 offspring over 6 d while older females (28 d pe) produced >60% fewer offspring over the same duration.…”
Section: Fertilitymentioning
confidence: 99%
“…27 A similar trend is observed as parental age increases: offspring of old (15 d pe) parents had »3% lower viability than offspring of young (1 d pe) parents, 16 and additional studies found a negative relationship between parental age and offspring viability. 60,81 One study failed to detect a difference in offspring viability between old parents (males and females >25 d pe) and young parents (>5 d pe), although the offspring of old parents developed significantly (16.4%) more rapidly than young parents. 82 Fertility is studied more precisely by observing the effects of female age on offspring viability at different life history stages including embryonic, larval, pupal, and adult.…”
Section: Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is often witnessed in laboratory conditions (e.g., see refs. [2][3][4] and, more rarely, in nature (5-7). For evolutionary biologists, the evolution of decreased performance and increased mortality with age, which should at first sight be counterselected, is a puzzle.…”
mentioning
confidence: 99%